The Effect of Structure and Grammar Mastery on Students’ Writing Skill - Karlina, Tia (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The title of this research is The Effect of Structure and Grammar Mastery on Students’ Writing Skill. The aim of this research was to determine the effect of structure and grammar mastery on students’ writing skill, the effect of structure mastery on students’ writing skill, and the effect of grammar mastery on students’ writing skill. The total sample of this research is 60 (sixty) students by using samole – random sampling. This research conducted at SMK RISE Kedawung, Cirebon. To collect the data, the students were given 50 (fifty) questions about structure and grammar in the multiple choice. The result of this research indicated that: 1) There are significant effect of structure and grammar mastery on students’ writing skill. It is proved by the Sig 0.000 < 0.05 and the value Fo = 92.124. 2) There is a significant effect of structure mastery on students’ writing skill. It is proved by the Sig 0.000 < 0.05 and value of to = 2.128. 3) There is significant influence of grammar mastery on students’ writing skill. It is proved by the Sig 0.000 < 0.05 and the value of to = 10.481. It can be said that the students’ writing skill at SMK RISE Kedawung, Cirebon is significally effect by structure and grammar mastery. The suggestion in this research was the students should be learning more seriously to overcome the errors or mistake of writing skill, the students have to get more motivation, study hard, practice always everytime and everyday.